USING FILM IN FOSTERING INTERCULTURAL AWARENESS FOR HIGH SCHOOL STUDENTS IN THE EFL CLASSROOM - Yeni Dyah Nur Kartikasari; Pratiwi Retnaningdyah; Ali Musthofa (Jurnal Education and Development, 2019)
Abstract: As foreign language learners and non-native speakers, high school students require to know other different cultures from their own to be actively involved in the process of acculturation and acquisition: social norms and cultural aspects, are inevitably. Intercultural awareness should be implemented in teaching and learning process. This paper aims at investigating techniques to develop students’ intercultural awareness in the EFL classroom. This is based on the research question: How is intercultural awareness through film in the EFL classroom? It is also argued that using film has much contributed in educational setting. This study used descriptive qualitative research design. The data were gained from the observation of students’ feedback through writing their responses after watching ‘Freedom Writers Diary’ as their journal writing. The findings showed that students found film was very beneficial. Firstly, films provided entertainment value. Secondly, they were well-thought of a reward that could carry students to a next higher step in target topic than traditional textbooks would. Thirdly, films might strengthen students’ emotions and lastly encourage them to deal with the topics, especially to gain intercultural awareness than their textbooks. Further research needs to examine aspects of intercultural awareness students elicit from the film. Keywords: film; intercultural awareness; high school students, EFL classroom; journal writing